"Estudio de mercado para la producción y comercialización de tilapia (Oreochromis) en el cantón Quevedo, Provincia de los Ríos 2015". - Alarcón Gómez, Cristóbal Oswaldo (2016)
This research was conducted in farms belonging to the producers: Catherine Parish Ramirez in La Esperanza, Jorge Hidalgo Manobanda and William Parish located at Km 3 via San Camilo Valencia, Jose Gonzales Figueroa and Emilio Chavez located in. Parish Guayacán the Virginia No. 2 , belonging to the Canton Quevedo , Los Rios Province , between the coordinates 0 ° 13 ' 23 " South Latitude 78 ° 30' 45 " West Longitude , is 90 meters high, with a population of 195,524 inhabitants. The general objective was to identify the factors that determine the production and marketing of tilapia in Canton Quevedo, Los Rios Province, 2015. The general objective was to identify the factors that determine the production and marketing of tilapia in Canton Quevedo, Los Rios Province, 2015. The specific objectives were to determine the production and marketing of tilapia in Canton Quevedo. Analyze supply and demand of the market for tilapia in Canton Quevedo. Conduct an economic analysis of the production of tilapia. The results were obtained through surveys of two producers and 96 consumers Tilapias Quevedo Canton. To determine the production, marketing, costs, revenues, market demand. For the execution of the study surveys of producers and consumers of Canton Quevedo, in which he allowed us feel about the reality of the farmer and consumer of Tilapia in the area, so you can get an idea of how production was made and what their marketing channels and profitability has tilapia, which was viewed favorably by respondents as they visited each of the existing fish farms in the Canton Quevedo, working with the questions asked in each of interviews